Myostatin Levels and the Risk of Myopenia and Rheumatoid Cachexia in Women with Rheumatoid Arthritis - Fabiola Gonzalez-Ponce; Jorge Ivan Gamez-Nava; Eli Efrain Gomez-Ramirez; Melissa Ramirez-Villafaña; Heriberto Jacobo-Cuevas; Norma Alejandra Rodriguez-Jimenez; Eva Maria Olivas-Flores; Yussef Esparza-Guerrero; Alejandro Martelli-García; Aline Priscilla Santiago-Garcia; Cesar Arturo Nava-Valdivia; Alejandra Martinez-Hernandez; et al. (Journal of Immunology Research)
Background. Myostatin is a regulator of muscle size. To date, there have been no published studies focusing on the relation between myostin levels and myopenia in rheumatoid arthritis (RA). Objective. Evaluate the value of serum myostatin as a biomarker of cachexia and low skeletal muscle mass (LSMM) in RA patients, along with whether high serum myostatin is associated to these conditions after adjusting for potential confounders. Methods. This cross-sectional study included 161 female RA patients and 72 female controls. In the RA group, we assessed several potential risk factors for LSMM and rheumatoid cachexia. Dual-energy X-ray absorptiometry was used to quantify the skeletal muscle mass index (SMMI) (considering LSMM≤5.5 kg/m2) and the presence of rheumatoid cachexia (a fat-free mass index≤10 percentile and fat mass index≥25 percentile of the reference population). Serum myostatin concentrations were determined by ELISA. To identify a cut-off for high serum myostatin levels, we performed ROC curve analysis. Multivariable logistic regression analysis was used to identify the risk factors for LSMM and rheumatoid cachexia. The risk was expressed as odds ratios (ORs) and their 95% confidence intervals (95% CIs). Results. Compared to the controls, the RA group had a higher proportion of LSMM and exhibited high serum myostatin levels (p<0.001). ROC curve analysis showed that a myostatin level≥17 ng/mL was the most efficient cut-off for identifying rheumatoid cachexia (sensitivity: 53%, specificity: 71%) and LSMM (sensitivity: 43%, specificity: 77%). In the multivariable logistic regression, RA with high myostatin levels (≥17 ng/mL) was found to increase the risk of cachexia (OR=2.79, 95% CI: 1.24-6.29; p=0.01) and LSMM (OR=3.04, 95% CI: 1.17-7.89; p=0.02). Conclusions. High serum myostatin levels increase the risk of LSMM and rheumatoid cachexia. We propose that high myostatin levels are useful biomarkers for the identification of patients in risk of rheumatoid cachexia and myopenia.